Análise de propostas pedagógicas para o trabalho com narrativas em Livro Didático do 6º ano do Ensino Fundamental II - Garcia, Elaine Cristina de Paiva (2017)
This dissertation has as a research line the Reading, Writing and Teaching of the Portuguese Language, and by theme the analysis of proposals for the teaching of storytelling in Didactic Book, of the 6th year of Elementary School II. It is problematized by the question: What is the effectiveness of the textbook guidelines, for the pedagogical work with narratives, in the 6th year of Elementary School II? The general objective of this research is to contribute to a reflexive pedagogical action on the guidelines brought by the didactic book, for the teaching of narrative, in the 6th year of Elementary School II. The specific objectives are to analyze present proposals of work with the narrative, in the textbook "Jornadas. Port of the 6th year of Elementary School ", by the authors Dileta Delmanto and Laiz B. de Carvalho, for the teaching of narrative, and indicate positive and negative aspects analyzed of the work proposals that focus the teaching of the narrative. The procedure adopted was theoretical-analytical and is established by the propositions of Textual Linguistics, to account for the textual schema of the narrative, the superstructure of the narrative text and the categories of the narrative text of history. The results obtained showed that the selected textbook provides the structural elements of the narrative, but does not direct the teacher to a pedagogical work directed to the teaching of reading, understanding and construction of the history narrative, since it considers the form, the structure and the product, and not the process for narrative teaching. Thus, this work presents a perspective of teaching history narrative with the purpose of assisting teachers and students